Hypertension Prevalence, Awareness, Treatment and Control, and Associated Factors: Results from a National Survey, Jordan - H. Y. Jaddou; A. M. Batieha; Y. S. Khader; A. H. Kanaan; M. S. El-Khateeb; K. M. Ajlouni (International Journal of Hypertension)
The study examined prevalence, awareness, treatment and control of hypertension (HTN), and associated factors and to evaluate the trend in hypertension between 2009 (period 2) and 1994–1998 (period 1). A national sample of 4117 adults aged 25 years and older was selected. Prevalence rate of HTN (SBP ≥ 140 or DBP ≥ 90 or on antihypertensive therapy) was 32.3% and was higher than the 29.4% prevalence rate reported in period 1. Prevalence rate was significantly higher among males, older age groups, least educated, obese, and diabetics than their counterparts. The rate of awareness among hypertensives was 56.1% and was higher than the 38.8% rate reported form period 1 data. Awareness was positively associated with age, smoking, and diabetes for both men and women, and with level of education and body mass index for men. Rate of treatment for HTN among aware patients was 63.3% and was significantly higher than the 52.8% rate reported in period1. Control rate of HTN among treated hypertensives was 39.6%; significantly higher than the 27.9% control rate in period 1. Control of HTN was positively associated with age but only for women. In conclusion, HTN is still on the rise in Jordan, and levels of awareness and control are below the optimal levels.